Aplikasi Konsentrasi Pupuk Organik Eco-Farming dan Anorganik Terhadap Peningkatkan Pertumbuhan dan Produksi Tanaman Padi (Oryza Sativa L.) - Ramli, Ramli; Kaimuddin, Kaimuddin; Rachmat, Rachmat; Hamzah, Pratiwi; Dahlan, Dahlan; Parawansa, Ismaya Nita Rianti (Politeknik Negeri Lampung., 2025)
Food crop commodities, especially rice, are needed by the people of Indonesia because they are a staple food. Food security is a requirement to produce healthy food. This study aims to analyze the effect of eco farming organic fertilizers and NPK on increasing the growth and production of rice plants. This research was carried out in Romanglompoa Village, Bontomarannu District, Gowa Regency. This research activity took place from February to September 2022. This research was designed using a Split Plot Design consisting of two factors. The first factor used as the main plot was inorganic namely 0% inorganic, 25% inorganic and 50% inorganic, and the second factor which was used as a subplot was Eco farming, Eco farming 25 ml, Eco farming 50 ml, and Eco farming 75 ml. These two factors were combined so that there were 9 treatment combinations. Each treatment series was repeated four times so that there were 36 treatments. The results showed that the 50 ml eco farming treatment showed the highest results on plant height (117.5 cm), panicle length (25.78 cm), rice grain (84.04 grains), number of seeds (122.63 grains), weight seeds (43.16 g), and the weight of 100 seeds (3.17 g). 50% inorganic treatment and 50 ml eco farming showed the highest results compared to other treatments.